Supply Chain Management Skills in Business and Humanitarian Contexts - Robert Davtyan; Wojciech Piotrowicz; Gyöngyi Kovács (Managing Global Transitions)
This study explores the differential skill requirements within supply chain management (SCM) across commercial and humanitarian contexts and career levels. Analysing 116 responses regarding context and 96 concerning career levels, the research confirms the applicability of the T-shaped model, highlighting the distinct skills critical for each sector. Significant discrepancies were found: humanitarian SCM prioritizes functional logistics, while business SCM places a larger emphasis on information technology, customs, transportation, and port/airport management. These findings suggest a dynamic skillset evolution, where functional skills, essential at entry-level positions, give way to general management capabilities as one progresses. This shift is more pronounced by experience rather than job title in the humanitarian sector. The implications for educational institutions and SCM practice are profound, necessitating curriculum updates to meet changing industry demands and support logistics practitioners transitioning between sectors.